Tourism thought as a factor of tourism development in Serbia - Lakićević, Marija; Žarevac, Milica (Hotel and Tourism Management, 2014)
Tourism as a phenomenon, by its spatial, economic, sociological, psychological, cultural, political and other connotations, has no counterpart in any other phenomenon of the modern world. Although not a science, Tourismology represents a scientific discipline that perceives tourism in the most comprehensive way. The aim of this research is to devise strategies (based on the results), the implementation of which could contribute to a greater appreciation of Serbian intellectual elite in the field of tourism, tourism research recognition and promotion of tourism thought in Serbia as the main factor of tourism activity development.